The emerging role of omega-3 fatty acids as a therapeutic option in neuropsychiatric disorders. (June 2019) - Reimers, Arne; Ljung, Hanna
The prevalence of neurologic and psychiatric diseases has been increasing for decades and, given the moderate therapeutic efficacy and safety profile of existing pharmacological treatments, there is an urgent need for new therapeutic approaches. Nutrition has recently been recognized as an important factor for the prevention and treatment of neuropsychiatric disorders. The omega-3 polyunsaturated fatty acids (n-3 PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) play critical roles in neuronal cell function and neurotransmission as well as inflammatory and immune reactions that are involved in neuropsychiatric disease states. A large number of experimental and epidemiological studies provide a strong basis for interventional clinical trials that assessed the clinical efficacy of n-3 PUFAs in various neurological and psychiatric disorders. Most of these trials found beneficial effects of dietary supplementation with EPA and DHA, and no serious safety concerns have emerged. This review gives an introduction to recent findings on the clinical efficacy of n-3 PUFAs in various neuropsychiatric disorders and the underlying biochemical mechanisms. In addition, the reader will be enabled to identify common methodological weaknesses of clinical studies on n-3 PUFAs, and suggestions for the design of future studies are given.